LANGUAGE SHIFT AND MAINTENANCE OF INTERMARRIAGES CHINESE FAMILIES - Mairtati Dewi; Sumarsih Sumarsih; Anni Holila Pulungan (Universitas Negeri Medan, 2018)
This study deals with language shift and language maintenance of intermarriages Chinese families.It aims at finding out the factors make language shift and language maintenance occur, finding out how language shift and language maintain occur and finding out why language shift and language maintain occur.This study was conducted in qualitative method.The sources of data were four intermarriage Chinese families; meanwhile the data was their utterances.The data was analyzed by using Interactive Model by Miles, Huberman, and Saldana. To find out what factors affecting language shift and maintenance, the researcher used Holmes’s theory. Based on the data analysis, the first finding shows that there were six factors affecting language shift and language maintenance occured in intermarriage chinese families namely bilingualism, migration, economic, environment, demographic, and attitude. And as the second finding was that the language shift and language maintenance occured since there are two languages exist in interethnic marriage. The existence of two languages means the competition between two languages. And as the third finding was the reasons why language shift and language maintenance occured are bilingualism in which the man or woman mastered two languages which led to language maintenance, migration in which the women migrate to follow their husband, economic factor dealing with the men and women’s occupations, environment where they lived in homogenous or heterogenous ethnic, demographic factor, and attitude which might be postive or negative. Keywords: language shift, maintenance, intermarriage, qualitative